Konstruksi Portofolio Optimal Saham-Saham LQ45 Tahun 2019 di Bursa Efek Indonesia - Wibisono Hardjopranoto (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2020)
Abstract—The ideal investment objective is to build an optimal investment portfolio. An investment portfolio that is able to provide maximum return at a certain level of risk. William Sharpe's (1963) Single Index Model (SIM) is a model with simple application, especially when compared to the Markowitz model (1952), mainly because of the consideration of the number of input variables. A simple SIM explains the relationship between market returns (rm) as an independent variable and returns on securities, ri with variations in the risk as the slope characteristic line, βi. The main limitation of MIS is that the risk in investing is represented only by changes in the index that are representative of the market. Using SIM, this study will describe the optimal portfolio construction by selecting LQ45 stocks on the Indonesia Stock Exchange (IDX) in 2019. The implementation of the SIM resulted in 19 LQ45 stocks selected from 45 stocks as optimal portfolio